O uso da inteligência competitiva para o desenvolvimento do modelo de negócios: um estudo no segmento de puericultura - Adum, Samir Hussain Nami (2020)
With this study, we verified how the adoption and use of competitive intelligence contribute to the development and improvement of the business model of companies in the childcare segment. The research method for data collection and analysis we chose was qualitative, descriptive, and exploratory, and data collection was done through interviews with a structured script. Six managers of small and medium-sized companies were interviewed in the childcare segment, mostly founders or successors who manage them. For data analysis and results from inferences, we used content analysis, and the research results were analyzed based on the formation of six categories, indicating that the adoption of competitive intelligence contributed to the development and improvement of the business model in the childcare segment. The results also showed the nonexistence of a specific information system for the collection, analysis, and processing of the information. However, respondents reported that they somehow use market information, competitors, and market trends in their decision-making, even informally. It was possible to identify evidence that the adoption of competitive intelligence by childcare companies, helped managers in their decision-making processes, to promote changes in their business model, to remain competitive in the market in which they operate. Finally, we found that competitive intelligence contributes to the creation, configuration, and appropriation of value in the business model in the childcare segment.